Isolation and Molecular Confirmation of Staphylococcus aureus from Bovine Mastitis in Various Locations of Tamil Nadu, India - Saranraj P,; Nisha R,; Nandhini D,; Yuvalakshmi L. (مجلة الانبار للعلوم البيطرية)
This present investigation was done for the Isolation and Molecular confirmation of Staphylococcus aureus from Bovine mastitis-infected cows in various Tamil Nadu, India locations. Two hundred milk samples, ranging from 15 to 20 ml, were collected aseptically from cows in farms in and around Tamil Nadu and surrounding areas after discarding the first few streaks of milk from 2021 to 2023. We used the CMT test to check the milk samples. Following a thorough mixing of the milk samples delivered to the laboratory, one loop containing the infected milk sample was plated on Nutrient agar and incubated at 37 ˚C for 18 to 24 hours. To identify the Staphylococcus aureus, the isolated bacterial colonies were preliminarily identified by Microscopic examination (Gram staining and Motility test), Plating in Selective medium (Mannitol Salt Agar) and Biochemical tests. The DNA of the bacteria was extracted and Polymerase Chain Reaction (PCR) was done to detect the presence of the nuc gene. Of the 200 milk samples obtained from nursing cows, 37.5 % were from Mastitis-positive animals; of these, 61.3 % were in the sub-clinical stage, while 38.7 % were in the clinical stage. Only 33 (16.5 %) of the 200 milk samples tested positive for Staphylococcus aureus. A total of 26 out of 75 animals (34.7 %) with Mastitis, and 7 out of 125 animals (5.6 %) without Mastitis. Fifteen (57.7 %) of the twenty-six Staphylococcus aureus isolates found in cows with mastitis were from clinical cases, whereas eleven (42.3%) were from sub-clinical cases. All of the Staphylococcus aureus isolates examined contained the 279 bp nuc gene, according to the conventional PCR findings. In conclusion, the research has shown that sub-clinical mastitis is more common than clinical mastitis and that Staphylococcus aureus was substantially more often isolated from mastitis milk, particularly in clinical instances.